Design and experiment of the double-seed hole seeding precision seed metering device for peanuts - Zhao, Xiaoshun; Ran, Wenjing; Hao, Jianjun; Bai, Wenjie; Yang, Xinlei (International Journal of Agricultural and Biological Engineering, 2022)
A secondary seeding precision double-seed peanut hole seeding seed metering device was designed to improve the performance of the peanut planting equipment and provide a solution for problems on the high seed charge that can cause poor cavitation and uniformity easily. The main structure and operation parameters in terms of groove length, seed charge height, seed-bed belt speed, and rotation speed of the seed metering wheel were determined through theoretical analysis. Single-factor and orthogonal tests were carried out through the JPS-12 seed metering device test bench, and the peanut variety Jinonghua-3 was selected as the test object. The single hole double-seed rate, qualified rate, the variation coefficient of hole spacing, and hole rate were chosen for evaluating the working performance. The results of the single-factor test showed that the seed metering performance is mainly affected by the groove length, the speed of the seed-bed belt and the rotation speed of the seed metering wheel, and the influence of the cavitation rate is minimal. The optimal seeding height is determined to be 40 mm. The results of the orthogonal test showed that the groove length was 27.3 mm, the seed-bed belt speed was 1.51 km/h, and the rotation speed of the seed metering wheel was 14.11 r/min. What’s more, a regression model based on the orthogonal test results was established, the qualified rate of the number of holes obtained after optimizing the model was 98.84%, the variation coefficient of hole spacing was 9.74%, and the hole rate was 1.40%. Notably, the working performances of the device can meet the requirement of precision seeding. Keywords: peanut, precision, seed metering device, orthogonal test, regression method DOI: 10.25165/j.ijabe.20221503.6608 Citation: Zhao X S, Ran W J, Hao J J, Bai W J, Yang X L. Design and experiment of the double-seed hole seeding precision seed metering device for peanuts. Int J Agric & Biol Eng, 2022; 15(3): 107–114.